Rancang Bangun Alat Bantu Pres Proses Hemming Untuk Mendukung Kerja Pelat Pada Praktikum Fabrikasi - Taufik Kurrohman; Amirul Siddiq Mirza; Heri Widiantoro (CV. Multi Kreasi Media, 2025)
Plate working practicum is one of the learning activities in the Mechanical Engineering Department, Bandung State Polytechnic. The use of practicum tools can facilitate students and lecturers in carrying out these activities. The problem encountered during plate working practicum is the limited availability of tools to press the edges of prism-shaped workpieces made by students. This leads students to use alternative tools such as plate bending tools, clamps, and hammers, which are less effective as they take longer and risk damaging the material due to uneven pressure. Based on this issue, the design and creation of a pressing tool is necessary to support the plate working practical activity. The mechanism of this tool uses the pressing force of a punch to shape or cut the workpiece according to the desired form and size. The design of this tool uses the Pahl & Beitz method, considering safety, ease of use, and ease of manufacturing. The final specifications of the press tool have dimensions of 300x250x253 mm, a tool weight of 47.3 kg, and a tool capacity to press plates up to 1 mm thick. Tests were conducted on ST37 steel plates with a thickness of 1 mm and plates with a thickness of 0.5 mm, demonstrating that the press tool can function effectively in the hemming process, both on 1 mm thick plates and prism-shaped workpieces.